This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Same way solution!
Exactly Same Way!!!
First, notice that ⌊ k ⌋ = n when n 2 ≤ k < ( n + 1 ) 2 .
Also notice that ⌈ k ⌉ = n when ( n − 1 ) 2 < k ≤ n 2 . If we want to find when n 2 ≤ ⌈ k ⌉ < ( n + 1 ) 2 (this is due to the bounds we found above), simply take the lower bound of when ⌈ k ⌉ = n 2 and the upper bound of ⌈ k ⌉ = ( n + 1 ) 2 . This gives us the following result: ⌊ ⌈ k ⌉ ⌋ = n when ( n 2 − 1 ) 2 < k ≤ ( ( n + 1 ) 2 − 1 ) 2
To find how many numbers are in that bound, simply subtract the lower bound from the upper bound:
( ( n + 1 ) 2 − 1 ) 2 − ( n 2 − 1 ) 2 = 4 n 3 + 6 n 2 − 1
Note that 5 7 6 = ( ( 4 + 1 ) 2 − 1 ) 2 , so we can take our sum from 1 to 5 7 6 and then there are 2 terms left over (both will result in 5). Taking the sum from 1 to 4 and counting our two that our formula misses:
5 + 5 + n = 1 ∑ 4 n ( 4 n 3 + 6 n 2 − 1 ) = 5 + 5 + 2 0 0 6 = 2 0 1 6
AWESOME!!!!!!!
Wrote a c++ program to find it
#include <iostream>
#include<math.h>
#include <cstdlib>
using namespace std;
float fun (int k){
return (sqrt(sqrt(k)));
}
int main() {
float i,sum=0;
for (i=1;i<579;i++){
sum+=fun(i);
}
cout<<sum;
return 0;
}
but it outputs 2269.38 if i take only integers i get 1962 why is it that we get different answers from computer and actual solution
Four line python code that returns 2016 :-)
1 2 3 4 5 |
|
I also got 1962 as the answer while solving manually.
1962 + 54 = 2016
Did the long way but still got the same answer
Problem Loading...
Note Loading...
Set Loading...
Let m = ⌈ k ⌉ and n = ⌊ m ⌋ . Then, we have:
\(\begin{array} {} n = \left \lfloor \sqrt{m} \right \rfloor & \Rightarrow n^2 \le m \le (n+1)^2 - 1 \\ m = \left \lceil \sqrt{k} \right \rceil & \Rightarrow (m-1)^2+1 \le k \le m^2 & \Rightarrow k \le \left[(n+1)^2 - 1\right]^2 \end{array} \)
Therefore,
n = 1 n = 2 n = 3 n = 4 n = 5 ⇒ ⇒ ⇒ ⇒ ⇒ 1 ≤ k ≤ 9 1 0 ≤ k ≤ 6 4 6 5 ≤ k ≤ 2 2 5 2 2 6 ≤ k ≤ 5 7 6 5 7 7 ≤ k ≤ 5 7 8
And,
k = 1 ∑ 5 7 8 ⌊ ⌈ k ⌉ ⌋ = k = 1 ∑ 9 1 + k = 1 0 ∑ 6 4 2 + k = 6 5 ∑ 2 2 5 3 + k = 2 2 6 ∑ 5 7 6 4 + k = 5 7 7 ∑ 5 7 8 5 = 9 ( 1 ) + 5 5 ( 2 ) + 1 6 1 ( 3 ) + 3 5 1 ( 4 ) + 2 ( 5 ) = 9 + 1 1 0 + 4 8 3 + 1 4 0 4 + 1 0 = 2 0 1 6